Evaluasi Usability pada Website KPU Menggunakan Metode System Usability Scale - Rusmawan Abdullah Sani (TIN: Terapan Informatika Nusantara, 2026)
The digitalization of public services at the General Elections Commission (KPU) is vital for election transparency, yet technical obstacles such as slow loading times and navigation complexity are still frequently reported. This study aims to evaluate the usability of the kpu.go.id website using the System Usability Scale (SUS) method to measure user perception of satisfaction, effectiveness, and efficiency in a standardized manner. This study was conducted in Indonesia with 100 respondents who had previously accessed the kpu.go.id website, using accidental sampling. A quantitative descriptive approach was employed by distributing a questionnaire consisting of ten standard SUS statements. The results show a mean SUS score of 71.5. Based on evaluation parameters, this score places the KPU website in the "Marginal High" category for acceptability, with a "Good" adjective rating and a "B" grade scale. Analysis based on Nielsen's usability dimensions reveals that Satisfaction (81.75) and Memorability (81) perform best, while the Errors (66) and Learnability (66.25) dimensions record the lowest scores. These findings indicate that while the website is functional and acceptable, significant optimization is required in error handling and navigation intuitiveness to bridge the digital divide and ensure service inclusivity for all segments of society. These results serve as a data-driven recommendation for the KPU to enhance its user interface to bolster public trust in democratic information systems.